Property rights, intersectionality, and women’s empowerment in Nepal - Pradhan, Rajendra; Meinzen-Dick, Ruth S.; Theis, Sophie (International Food Policy Research Institute, 2018)
In this paper, we explore how different norms around property rights affect the empowerment of women of different social positions over the life cycle. We first review the conceptual foundations of property, empowerment, and intersectionality, and then present the methodology and empirical findings from ethnographic field work in Nepal. Going beyond formal ownership of property, we look at changes in property rights over personal and joint property at different stages of women’s lives. Finally, the paper makes recommendations for how research and development projects, especially in South Asia, can avoid misinterpreting asset and empowerment data by incorporating nuance around the concepts of property rights over the household life cycle.